A Critical Analysis of Technological Integration in Healthcare Service Efficiency - Alyami, Salem Saleh Mahdi; Alhulays, Saleh Hussien M; Alfaqair , Khaled Saleh; Alqashanin, Mesfer Mana; Alqashanin, Salem Mana; Alzamanan, Mohammed Ali; Almuhathil, Rakan Hashan Mohammed; Faqeeh, Hussain Ahmad; Alfaqir, Ahmed Hussain Saleh; Al Futaih, Issa Misfer Ali (Journal of Ecohumanism, 2024)
The focus of this paper is to investigate whether integrating technology enhances the efficiency of healthcare services. It looks into the opportunities and risks of adopting and integrating technology to deliver patient services, manage operational activities, and improve patient health. Consequently, this study defines areas of knowledge deficit and makes recommendations for potential improvements for the future based on major trends and empirical evidence presented in the study.